KNOWLEDGE MAPPING OF CYBER BULLYING: A BIBLIOMETRIC ANALYSIS FROM 2015 TO 2025 - Khatimah, Rifqah Husnul; Kustati, Martin; Bashori, Bashori (The Future of Education Journal, 2026)
Cyberbullying has emerged as a critical social issue alongside the rapid expansion of digital technologies and social media use, particularly among students and adolescents. The growing prevalence of cyberbullying has stimulated extensive scholarly attention across multiple disciplines, yet a systematic overview of research trends remains limited. This study aims to map the development, thematic structure, and research trends in cyberbullying studies using a bibliometric approach. A descriptive qualitative bibliometric method was employed. Data were retrieved from the Scopus database by searching for the keyword “cyberbullying” in article titles, abstracts, and keywords. The analysis was restricted to peer-reviewed journal articles published in English within a specified time period. The collected data were analyzed using VOSviewer to examine keyword co-occurrence networks and to visualize thematic clusters. The findings reveal that cyberbullying research has evolved into several major thematic clusters, including cyberbullying and mental health, cyberbullying in educational contexts, the role of social media and digital platforms, and prevention and intervention strategies. Network visualization indicates strong linkages between cyberbullying and keywords such as students, mental health, social media, and online behavior. This bibliometric mapping provides a comprehensive overview of the intellectual structure of cyberbullying research and highlights emerging research directions, offering valuable insights for researchers, educators, and policymakers in developing effective prevention and intervention strategies in the digital era.